Neuromuscular, physiological and perceptual responses to an elite netball tournament. Issue 19 (2nd October 2019) - Birdsey, Laurence P.; Weston, Matthew; Russell, Mark; Johnston, Michael; Cook, Christian J.; Kilduff, Liam P.
ABSTRACT: To examine responses to an International netball tournament, female athletes ( n = 11) played three matches over consecutive days. External (accelerometry) and internal (heart rate; HR, session; sRPE, and differential; dRPE, rating of perceived exertion) load measures quantified match intensity. On match-day mornings, and three days after match 3, well-being (brief assessment of mood; BAM+), biochemical (creatine kinase concentration; CK), neuromuscular (jump height; JH, peak power output; PPO) and endocrine function (salivary cortisol; C, testosterone; T, concentrations) were assessed. External load was similar between matches whereas dRPE and sRPE were greatest for match 3. Following match 1, CK increased, whereas BAM+, JH, C and T decreased. Following two matches, BAM+, PPO, and T decreased with CK increasing versus baseline. Following consecutive matches, CK (likely moderate; 27.9% ± 19.5%) and C (possibly moderate; 43.3% ± 46.8%) increased, whilst BAM+ (possibly moderate; −20.6% ± 24.4%) decreased. Three days post-tournament BAM+, T, PPO, and JH decreased. Mid-court elicited higher mean HR (possibly moderate; 3.7% ± 3.8%), internal and external intensities (possibly very large; 85.7% ± 49.6%) compared with goal-based positions. Consecutive matches revealed a dose–response relationship for well-being and physiological function; a response evident three days post-tournament.